Оцінювання за вейвлет-перетворенням сигналів акустичної емісїї різних типів руйнування - Назарчук, Зіновій; Станкевич, Олена; Добровольська, Любов (КІНПАТРІ ЛТД, 2013)
Features of the acoustic emission signals which accompany a fracture of the different type of structural materials have studied. By analysis of continuous and discrete wavelet transforms the signals were classified with the account of the criterion parameter which was offered by the authors earlier. It is established good correlation between parameters of the continuous wavelet transform and the power criterion of discrete wavelet transform.
Wavelet transform of acoustic emission signals of the different fracture types